Seawater carbonate chemistry and elemental contents and macromolecules of the coccolithophore Emiliania huxleyi - Xie, Emei; Xu, Kai; Li, Zhengke; Li, Wei; Yi, Xiangqi; Li, Hongzhou; Han, Yonghe; Zhang, Hong; Zhang, Yong (PANGAEA, 2021)
Elemental contents change with shifts in macromolecular composition of marine phytoplankton. Recent studies focus on the responses of elemental contents of coccolithophores, a major calcifying phytoplankton group, to changing carbonate chemistry, caused by the dissolution of anthropogenically derived CO2 into the surface ocean. However, the effects of changing carbonate chemistry on biomacromolecules, such as protein and carbohydrate of coccolithophores, are less documented. Here, we disentangled the effects of elevated dissolved inorganic carbon (DIC) concentration (900 to 4,930μmol/kg) and reduced pH value (8.04 to 7.70) on physiological rates, elemental contents, and macromolecules of the coccolithophore Emiliania huxleyi. Compared to present DIC concentration and pH value, combinations of high DIC concentration and low pH value (ocean acidification) significantly increased pigments content, particulate organic carbon (POC), and carbohydrate content and had less impact on growth rate, maximal relative electron transport rate (rETRmax), particulate organic nitrogen (PON), and protein content. In high pH treatments, elevated DIC concentration significantly increased growth rate, pigments content, rETRmax, POC, particulate inorganic carbon (PIC), protein, and carbohydrate contents. In low pH treatments, the extents of the increase in growth rate, pigments and carbohydrate content were reduced. Compared to high pH value, under low DIC concentration, low pH value significantly increased POC and PON contents and showed less impact on protein and carbohydrate contents; however, under high DIC concentration, low pH value significantly reduced POC, PON, protein, and carbohydrate contents. These results showed that reduced pH counteracted the positive effects of elevated DIC concentration on growth rate, rETRmax, POC, PON, carbohydrate, and protein contents. Elevated DIC concentration and reduced pH acted synergistically to increase the contribution of carbohydrate–carbon to POC, and antagonistically to affect the contribution of protein–nitrogen to PON, which further shifted the carbon/nitrogen ratio of E. huxleyi.
Keywords: Biomass/Abundance/Elemental composition; Bottles or small containers/Aquaria (<20 L); Chromista; Emiliania huxleyi; Growth/Morphology; Haptophyta; Laboratory experiment; Laboratory strains; Not applicable; Other; Pelagos; Phytoplankton; Primary production/Photosynthesis; Single species